Political, Socal and Economic Rights of the Dhimmis in the Buyid (334-447/ 945- 1055) - Ako Burhan Muhammad; Azad Othman Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
(Ahl al‐dhimma) are free non-Muslims, minorities (Christian, Jewish, Sabia's, Zardashti) who enjoy Muslim protection. They all have the same rights as Muslims, and this right came under this law (They have what the Muslims have, and they have what they owe). Ahl al‐dhimma had all rights and duties there were not any differences with Muslims. But for not doing military services they have to give Jizya to the state, whereas Muslims had to pay Zakah and tax to the state more than them. Ahl al‐dhimma had all political, management, economical and social rights. The state had given them all rights in all aspects of life. And they could succeed to get all their rights and they had the ability to participate in governmental buildings and all sectors, and no one can ever deny their pivotal role in management, trade and agriculture. Furthermore, they had a great relationship with Muslims, and they went to Muslim weddings and invitations. Therefore, they as a minority could get lots of ministerial positions and gain Bwaihi trust. Moreover, they had a great role in management, helping the states in terms of agriculture, trade and theft prevention. In addition, Non-Muslims had a great social interaction with Muslims in alleys and cities where they had lived.